2001
DOI: 10.1055/s-2001-15574
|View full text |Cite
|
Sign up to set email alerts
|

Aktivität und Depression - Möglichkeiten und Grenzen aktigraphischer Verhaltensanalysen -

Abstract: Measurements of motor behavior by actigraphy can be used in depression for diagnostic procedures and treatment evaluation. The role of actigraphic setting variables needs further clarification. Actigraphy may be used for behavioral analysis including individual regulation of motor activity as an objective parameter for evaluation of depression and other psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…motor retarded) in the differentiation of the various types of depression, most research shows that bipolar depressive patients show psychomotor slowness compared to the depressive unipolar patients [24,55] . However, studies that assessed these subtypes of depression through actigraphy found no significant differences in the levels of motor activity and immobility between the 2 diagnostic categories, indicating the need for further studies [26,29] .…”
Section: Discussionmentioning
confidence: 99%
“…motor retarded) in the differentiation of the various types of depression, most research shows that bipolar depressive patients show psychomotor slowness compared to the depressive unipolar patients [24,55] . However, studies that assessed these subtypes of depression through actigraphy found no significant differences in the levels of motor activity and immobility between the 2 diagnostic categories, indicating the need for further studies [26,29] .…”
Section: Discussionmentioning
confidence: 99%